Physiological responses during female judo combats: impact of combat area size and effort to pause ratio variations - Ouergui, I.; Kamzi, S.; Houcine, N.; Abedelmalek, S.; Bouassida, A.; Bouhlel, E.; Franchini, E. (The Journal of Strength and Conditioning Research, 2021)
This study investigated the effect of area size (4 × 4, 6 × 6, and 8 × 8 m) and effort-pause ratio (free combat, 2:1 and 3:1) on the physiological and perceptive responses during female judo combats. Twelve female judo athletes (mean ± SD: age: 17.1 ± 0.4 years; height: 160 ± 7 cm; body mass: 59.8 ± 11.5 kg; body fat: 25.7 ± 5.5%; and judo experience: 8.4 ± 0.5 years) volunteered to perform nine 4-minute randoris randomly determined. Blood lactate [La] before and after combats, heart rate before combat (HRpre), mean HR (HRmean), peak HR (HRpeak), and rating of perceived exertion (RPE) immediately after the combats were assessed for each condition. Results showed that [La] pre and HR values did not differ according to time structure and area sizes (p > 0.05). However, [La] post was higher on free randori compared with 3:1 ratio (p = 0.006) and in the 4 × 4-m area compared with 6 × 6-m (p < 0.001) and 8 × 8-m (p = 0.036) areas. Moreover, RPE was higher in the 4 × 4 m compared with 8 × 8 m (p = 0.038). In conclusion, combining time structure and area sizes may alter physiological and perceptual responses during female judo randori. Moreover, combat-based exercises may be effective in preparing athletes to cope with physiological and technical demands of the combat by stressing properly the energy systems solicited during official competitions.